Mocking Women’s Social Judgment in Victorian Era Using Satire Language Style in Pride and Prejudice - Yulia Sofiani Zaimar; Ajeng Dinar Wisesa Wardhani (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
This paper offers ironic language style overview of the satire in Pride and Prejudice Novel, cerated by Jane Austen. The Pride and Prejudice novel, which was written in Victorian Era, had brought many changes. It was the first England novels, written by a woman. The novels became interesting, because it contains many satire inside, connecting the atmosphere in Victorian era. Austen was well known for the use of satire and was often pointed to feminist tendencies within her work, which provided a gap worthy of research as there were several studies concerning Austen’s use of satire and existence of feminism in Pride and Prejudice separately, but not as inter-related elements. The method, used in this research is a method that take the paragraph show the ironic language style, containing satire..The result showed that there is language style of satire, like as language criticsm and language of mockery. In addition, there is social value, which was coordination and cooperation, were found. Humors have been found everywhere in the novel; in its words devine imagery, but mostly in its conversations between characters. Her novels were not only her way of entertaining people but it was also a way to express her opinions and views on what surrounded her and affected her. KeyWord: Woman writter, Irony, Satire, and Victorian Era